2021
DOI: 10.3390/life11090924
|View full text |Cite
|
Sign up to set email alerts
|

TAT for Enzyme/Protein Delivery to Restore or Destroy Cell Activity in Human Diseases

Abstract: Much effort has been dedicated in the recent decades to find novel protein/enzyme-based therapies for human diseases, the major challenge of such therapies being the intracellular delivery and reaching sub-cellular organelles. One promising approach is the use of cell-penetrating peptides (CPPs) for delivering enzymes/proteins into cells. In this review, we describe the potential therapeutic usages of CPPs (mainly trans-activator of transcription protein, TAT) in enabling the uptake of biologically active prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 127 publications
(171 reference statements)
0
8
0
Order By: Relevance
“…TAT and TAT‐modified drugs can be internalized by cells and tissues rapidly and efficiently while retaining their biological activity (Vivès et al, 1997). In addition, many studies have shown that TAT and TAT‐modified drugs can cross the BBB and are therefore useful for the delivery of TAT protein‐modified drugs to the brain (Lichtenstein et al, 2021). A group led by Takanori Kanazawa has been working on the development of TAT‐modified polyethylene glycol‐ b ‐poly(ε‐caprolactone) (PEG‐PCL) micelles for the intranasal treatment of various brain diseases since 2012, and they have intensively studied the brain distribution and metabolic behavior of each system loaded with small molecules and nucleic acids (Table 3).…”
Section: Transcytosis In the Nose‐to‐brain Pathwaymentioning
confidence: 99%
“…TAT and TAT‐modified drugs can be internalized by cells and tissues rapidly and efficiently while retaining their biological activity (Vivès et al, 1997). In addition, many studies have shown that TAT and TAT‐modified drugs can cross the BBB and are therefore useful for the delivery of TAT protein‐modified drugs to the brain (Lichtenstein et al, 2021). A group led by Takanori Kanazawa has been working on the development of TAT‐modified polyethylene glycol‐ b ‐poly(ε‐caprolactone) (PEG‐PCL) micelles for the intranasal treatment of various brain diseases since 2012, and they have intensively studied the brain distribution and metabolic behavior of each system loaded with small molecules and nucleic acids (Table 3).…”
Section: Transcytosis In the Nose‐to‐brain Pathwaymentioning
confidence: 99%
“…[112]. Successful protein transport to the brain has been accomplished after protein-to-TAT peptide conjugation [113].…”
Section: Peptidesmentioning
confidence: 99%
“…CPPs are mainly small and cationic peptides consisting of 5-30 amino acids that are able to move through the lipid bilayer. Because of their ability to carry biologically active cargos, such as proteins, 21,22 nucleic F I G U R E 1 Representation of membrane interaction of (a) fusion peptides, (b) antimicrobial peptides, and (c) cell-penetrating peptides acids, 23 or nanoparticles 24,25 across the membrane, they are also referred to as protein transduction domains (PTDs). The first CPPs to be discovered were the HIV-1 TAT protein in 1988 26 and penetratin in 1994.…”
Section: Cell-penetrating Peptidesmentioning
confidence: 99%